Crop, Tillage, and Landscape Effects on Near‐Surface Soil Quality Indices in Indiana. Issue 6 (22nd December 2016) - Hammac, W. Ashley; Stott, Diane E.; Karlen, Douglas L.; Cambardella, Cynthia A.
Abstract : Core Ideas: Soil quality scores were highest in perennial grass systems, followed by a soybean‐dominated rotation, followed by a corn‐based rotation. No‐till crop production had no higher soil quality score than chisel–disk tillage but the uncultivated perennial grass system scored higher than both. In this crop production‐dominated region, soil quality is driven by biological properties like soil C and β‐glucosidase activity and physical properties like bulk density and macroaggregate stability. Soil quality is a critical link between land management and water quality. We aimed to assess soil quality within the Cedar Creek Watershed, a pothole‐dominated subwatershed within the St. Joseph River watershed that drains into the Western Lake Erie Basin in northeastern Indiana. The Soil Management Assessment Framework (SMAF) with 10 soil quality indicators was used to assess inherent and dynamic soil and environmental characteristics across crop rotations, tillage practices, and landscape positions. Surface physical, chemical, and nutrient component indices were high, averaging 90, 93, and 98% of the optimum, respectively. Surface biology had the lowest component score, averaging 69% of the optimum. Crop rotation, tillage, and landscape position effects were assessed using ANOVA. Crop selection had a greater impact on soil quality than tillage, with perennial grass systems having higher values than corn ( Zea mays L.) or soybean [ Glycine max (L.) Merr.]. Furthermore, soybean rotations often scored higher than corn rotations. Uncultivated perennial grass systems had higher overall soil quality index (SQI) values and physical, chemical, and biological component values than no‐till or chisel–disk systems. Chisel–disk effects on overall and component SQI values were generally not significantly different from no‐till management except for a few physical indicators. Toe‐slopes had higher physical, biological, and overall SQI values than summit positions but toe‐slope values were not significantly different from those of mid‐slope positions. This work highlights the positive effects of perennial grass systems, the negative effects of corn‐based systems, and the neutral effects of tillage on soil quality.